An attractive, sensitive and high-throughput strategy based on microextraction by packed sorbent followed by UHPLC-PDA analysis for quantification of hydroxybenzoic and hydroxycinnamic acids in wines - Gonçalves, João (2019)
An attractive, fast, low-consumption and very promising high-throughput strategy based on microextraction by packed sorbent (MEPS), and reversed phase ultra-high pressure liquid chromatography (UHPLC), was developed and validated for the determination and quantification of hydroxybenzoic (gallic acid, protocatechuic acid, gentisic acid, vanillic acid, syringic acid), and hydroxycinnamic acids (p-coumaric acid, m-coumaric acid, o-coumaric acid, ferrulic acid and cinnamic acid) in wines. Important factors affecting the performance of MEPS such as the type of sorbent material (C2, C8, C18, SIL and C8/SCX), number of extraction cycles (extract–discard), sample volume and elution volume were tested and optimized. The optimal MEPS extraction conditions were obtained using C8 phase as sorbent and 50 μL of the sample in five extraction cycles. The analytes were separated on a new Trifunctional High Strength Silica analytical column (HSS T3; 100% silica particle), specially designed for polar compounds, using a binary mobile phase composed of aqueous 0.1% formic acid (eluent A) and methanol (eluent B) in the gradient elution mode (10 min of total analysis). This new stationary phase, proved to be an excellent alternative to conventional C18 columns for the determination of benzoic and cinnamic acids derivatives in wines. The analytical method was fully validated in terms of linearity, limits of detection (LOD), limits of quantification (LOQ), extraction yield, accuracy and inter/intra-day precision, using a synthetic wine spiked with hydroxybenzoic and hydroxycinnamic acids, and demonstrated good linearity with r2‐values > 0.998 within the established concentration range (0.2–40 μg mL− 1). Under the optimized conditions, LOD of 0.01–0.2 μg mL− 1, LOQ of 0.03–0.7 μg mL− 1, and precision, expressed as the relative standard deviation (RSD %), within 0.3–6% were observed. The proposed method was also applied to the analysis of hydroxybenzoic and hydroxycinnamic acids in red and white wines and recoveries of 80–100% and 77–99%, respectively, were obtained. The new approach offers an attractive alternative for analysis of phenolic acids from wine samples, providing a number of advantages including decreased sample preparation, faster sample throughput and easy to perform as compared to traditional methodologies. Moreover it could potentially be extended to other extraction media.